PENGEMBANGAN PULAU KECIL PERBATASAN (KAJIAN SOSIAL DAN KEBIJAKAN PADA PULAU LIRANG) - Kour, Femsy (LPPM Universitas Hein Namotemo, 2017)
Lirang Island is one of the small island on Moluccas that deserve full attention by the government is Lirang Island. Its fisheries potential can be used by fisherman and it can be developed in socio-economic area. Lirang?s border area was isolated from education, health, transportation infra structure, electricity, and teleccomunication. Therefore it was necessary  have a proper management and development of small islands in accordance with the potential, characteristics, and problems of the area. The aim of this reseach are to analyze Lirang?s social-community condition using descriptive method; to analyze border area development policy, and formulate Lirang?s development strategy using public policy analysis and SWOT analysis. Social condition in Lirang?s border area was too low. This can be seen from the low human resources, low regional infrastructure and fishery infrastructure.Some policies that support development of Lirang island as a small island border were: (a) Realization of  integrity and  sovereignty territory marked bythe clarity and firmness of boundaries State; (B) Declining illegal activities and maintain the environment in border areas; (C)people service quality increase with Social Welfare Problems; (D) Increasing the quality of government and fishery infrastructure facilities; (F) Social quality increase of border communities marked by declining number of poor people in Lirang Island. The formulation of a very important strategy to develop Lirang Island were: (a) to increase the guidance and counseling to the community in the border area; (B) Optimizing fisheries business and maximizing regional development; (C) Enhance cooperation in social development, and security with neighboring countries.